Inclusive education journey: comparative insights from gifted and differently abled learners - Ramil B. Arante; John O. Estillore (Institute of Advanced Engineering and Science, 2026)
This study aimed to comparatively examine the educational needs of learners with disabilities (LWDs) and potentially gifted learners (PGLs) within higher education institutions, highlighting their distinct yet overlapping requirements for inclusive learning. Using a qualitative-comparative research design, 20 participants, 10 from each group, were selected through purposive sampling. Semi-structured interviews were conducted and analyzed using Braun and Clarke’s thematic framework to identify convergent and divergent themes. Results revealed that both groups face systemic and pedagogical barriers, including rigid curricula, limited institutional support, and insufficient guidance in developing social-emotional skills. While LWDs emphasized accessibility, assistive technologies, and equitable participation, PGLs highlighted the need for enrichment, mentorship, and intellectual challenge. Despite differing emphases, both groups shared the need for inclusive policies, emotional support, and a sense of belonging. The study proposes an integrated model of inclusivity that unites adaptive pedagogy, personalized mentorship, and wellness programs under coherent institutional policies. This framework reframes inclusion from fragmented interventions toward a holistic, equity-driven approach that values diversity as a resource for learning. Findings contribute to the global discourse on inclusive education by demonstrating that authentic inclusivity in higher education emerges when accessibility and excellence are addressed through a unified, transformative educational system.